The Effect of Financial Knowledge, Financial Attitude, Financial Self-Efficacy, and Financial Socialization on the Financial Management Behavior of Working People in Ketapang Regency - Putri, Amelia; Hariyanto, Dedi; Safitri, Heni (UNIVERSITAS PAKUAN, 2025)
Good financial management is essential for achieving financial well-being, especially in the face of dynamic economic challenges. In Ketapang Regency, many working people experience difficulties in managing their personal finances, partly due to low financial literacy and attitudes. This study aims to analyze the influence of Financial Knowledge, Financial Attitude, Financial Self-Efficacy, and Financial Socialization on the Financial Management Behavior of working people in Ketapang Regency. The method used in this study is an associative study with a quantitative approach. Data was collected through a questionnaire distributed to 150 respondents who work in Ketapang Regency. Validity and reliability tests were conducted to ensure the research instrument, while multiple linear regression analysis was used to test the relationship between variables. The results of the study indicate that, simultaneously, Financial Knowledge, Financial Attitude, Financial Self-Efficacy, and Financial Socialization have a positive and significant influence on financial management behavior. Partially, each variable shows a positive and significant influence on Financial Management Behavior, including Financial Knowledge, Financial Attitude, Financial Self-Efficacy, and Financial Socialization. This study contributes to the development of more effective financial education programs, particularly for the working population in Ketapang District.